Peran Guru Pendidikan Agama Islam dalam Membentuk Karakter Peserta Didik di MA At-Taqwa - kurniawati, Yuli; Rohmatulah; Sri Lestari (UNISAN JURNAL, 2025)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in shaping students’ character at MA At-Taqwa Yastu Karang Tanjung, Pandeglang, Banten. This research employs a qualitative approach with a descriptive method. The subjects of the study include PAI teachers, the head of the madrasah, and several students selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results of the study indicate that PAI teachers play an important role as educators, mentors, role models, and motivators in developing students’ character. Character values such as religiosity, discipline, responsibility, and politeness are instilled through classroom learning activities, worship habituation, and teachers’ exemplary behavior in daily life at the madrasah. Supporting factors in character formation include a religious school environment and institutional support, while inhibiting factors involve students’ lack of awareness and negative external influences. Therefore, the role of PAI teachers is highly significant in creating a generation with Islamic character and noble morality.